Optimalisasi Budidaya Udang Windu (Penaeus monodon) Melalui Pendekatan Teknologi dan Manajemen Terpadu di Kecamatan Labakkang Kabupaten Pangkep - Nompo, Marwah; Hasanuddin, Hasanuddin; Rabi’ah, Sitti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
The research method used is a mixed method by combining qualitative and quantitative research which aims to analyze the conditions of tiger shrimp cultivation in Labakkang District and evaluate the application of technology to improve production efficiency. The data collection techniques used are interviews and observations. Meanwhile, the data analysis techniques used in this study include descriptive analysis and inferential statistics. The results show that most farmers still rely on traditional and semi-intensive cultivation systems, which face major challenges in the form of technological limitations, fluctuations in water quality, and high operational costs. Suboptimal water circulation systems in traditional ponds lead to low dissolved oxygen levels and high accumulation of organic waste. The dissolved oxygen level in traditional ponds ranges from 3.5–4.2 mg/L, while in semi-intensive ponds, it is better, namely 4.5–5.0 mg/L. As a solution, the application of biofloc systems is proven to increase productivity and reduce feed costs. Ponds using biofloc technology showed lower ammonia levels (0.01–0.03 mg/L) compared to conventional ponds (0.05–0.08 mg/L), with an increase in production of 30% and a survival rate of 85% of shrimp. In addition, the use of water aeration and recirculation systems showed an increase in dissolved oxygen levels of up to 6.0 mg/L, which improved shrimp health and reduced mortality rates due to environmental stress. More controlled feeding efficiency was also shown to lower feed conversion (FCR) from 1.5 to 1.2, which contributed to increased shrimp growth and reduced operational costs. This study suggests the adoption of modern technology, better water quality management, and feeding efficiency to increase productivity and sustainability of tiger shrimp farming in Labakkang.